2021
DOI: 10.1186/s40580-021-00260-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall iron oxide nanoparticles induced ferroptosis via Beclin1/ATG5-dependent autophagy pathway

Abstract: Iron-based nanoparticles, which could elicit ferroptosis, is becoming a promising new way to inhibit tumor cell growth. Notably, ultrasmall iron oxide nanoparticles (USIONPs) have been found to upregulate the autophagy process in glioblastoma (GBM) cells. Whether USIONPs could also elicit ferroptosis and the relationship between the USIONPs-induced autophagy and ferroptosis need to be explored. In the current study, our synthesized USIONPs with good water solubility could significantly upregulate the ferroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…The curcumin analogues ALZ003 and quinkalim can lead to ferroptosis in glioma cells, thus opening new avenues for the treatment of temozolomide (TMZ)-resistant glioblastoma ( 30 , 31 ). Iron oxide nanoparticles are safe and effective ferroptosis and apoptosis inducers and can be used as a combination therapy for glioblastoma ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…The curcumin analogues ALZ003 and quinkalim can lead to ferroptosis in glioma cells, thus opening new avenues for the treatment of temozolomide (TMZ)-resistant glioblastoma ( 30 , 31 ). Iron oxide nanoparticles are safe and effective ferroptosis and apoptosis inducers and can be used as a combination therapy for glioblastoma ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that these factors might have different targets for suppressing the same mode of death. It has been established that certain drugs can induce ferroptosis in tumor cells by activating autophagy [ 42 ]. To determine whether Rh4 can also induce ferroptosis in CRC cells by activating autophagy, we pretreated HT29 and HCT116 cells with 3-MA and then treated the cells with Rh4.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we previously observed that AgNPs selectively eliminate certain TNBCs, ovarian cancer cells, and NCSLC with a mesenchymal phenotype [23,27,29,33]. Reports indicate that certain nanoparticles, including iron-core nanoparticles [70,71], titanium dioxide (TiO2) [72], ultrasmall poly (ethylene glycol)-coated silica nanoparticles [73], cobalt NPs [74], and manganese silicate nanobubbles [75], induce lipid oxidation in a variety of cell types. The cause of the general vulnerability of various cancers with an EMT phenotype to engineered nanomaterials has not been firmly established, but our data indicate that nanoparticle-induced lipid peroxidation and proteotoxicity may play a key role in this.…”
Section: Discussionmentioning
confidence: 99%